The New Stage in the Archeology of Kaliningrad Region (On the Conference Archeology of the Baltic Region: New Discoveries and Investigations, Kaliningrad, November 17-19, 2010 - Linas Tamulynas (Lietuvos Istorijos Studijos)
-